ANALISIS KESESUAIAN LAHAN SEMBILAN JENIS TANAMAN UNTUK AGROFORESTRI DI NAMBO, JAWA BARAT - Tigor Butarbutar; Ismatul Hakim; Niken Sakuntaladewi; Hariatno Dwiprabowo; Lukas Rumboko; Setiasih Irawanti (Pusat Penelitian dan Pengembangan Hutan, 2018)
ABSTRACTOne of the weakness of agroforestry practices in West Java was that the pattern of species mixing was not based on site characteristics such as soil, climate, and topography and caused low production. This research was conducted to ascertain the land suitability classes for nine species, which are: Tectona grandis, Swietenia mahagony, Artocarpus integra, Nephelium lappaceum, Areca catechu, Musa sp., Zea mays, Capsicum sp. and Pennisetum purpureum, along with their optimum combination. The research was located in two sites (Acacia mangium) and community mixed plantation in Nambo village, Klapanunggal subdistrict, Bogor regency, West Java using the “Minimum Limiting Factor